2012
DOI: 10.1080/00028487.2012.713887
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Larval Sea Lampreys from Short‐Term Exposure to the Pesticide 3‐Trifluoromethyl‐4‐Nitrophenol: Implications for Sea Lamprey Control in the Great Lakes

Abstract: For over 50 years, invasive sea lamprey Petromyzon marinus populations have been controlled in the Great Lakes using the pesticide 3-trifluoromethyl-4-nitrophenol (TFM), which is applied to streams containing larval sea lampreys. The specificity of TFM is due to the sea lamprey's relative inability to detoxify it using glucuronidation; this inability causes death by interfering with the production of ATP, the main energy currency of cells. TFM treatments typically last 12 h, but given the sea lamprey's relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…In recent years, a number of studies have described the physiological impact and mechanism of TFM toxicity in sea lamprey, non-target fishes and other organisms ( Viant et al , 2001 ; Wilkie et al , 2007 ; Birceanu et al , 2009 , 2011 , 2014 ; Clifford et al , 2012 ; Henry et al , 2015 ). Because of the structural similarity of TFM to 2,4-dinitrophenol (2,4-DNP), a known uncoupler of oxidative phosphorylation, it was first suggested by Applegate et al (1966 ) that TFM may cause death by interfering with mitochondrial ATP production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of studies have described the physiological impact and mechanism of TFM toxicity in sea lamprey, non-target fishes and other organisms ( Viant et al , 2001 ; Wilkie et al , 2007 ; Birceanu et al , 2009 , 2011 , 2014 ; Clifford et al , 2012 ; Henry et al , 2015 ). Because of the structural similarity of TFM to 2,4-dinitrophenol (2,4-DNP), a known uncoupler of oxidative phosphorylation, it was first suggested by Applegate et al (1966 ) that TFM may cause death by interfering with mitochondrial ATP production.…”
Section: Introductionmentioning
confidence: 99%
“… Birceanu et al (2009 , 2011) later showed that TFM uncouples oxidative phosphorylation in mitochondria isolated from the livers of sea lamprey and in non-target rainbow trout, leading to a mismatch between ATP supply and ATP demand ( Birceanu et al , 2009 , 2014 ). Notably, TFM significantly depleted anaerobic energy stores such as glycogen and phosphocreatine in metabolically active tissues such as the brain, liver and kidney, but less so in the muscle ( Wilkie et al , 2007 ; Birceanu et al , 2009 , 2014 ; Clifford et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TFM-induced increase in cortisol in vivo in the present context could be advantageous to the fish short-term immediately after TFM exposure, as it allows them to cope with and recover from the exposure. Short-term elevations of cortisol would be advantageous because cortisol promotes glycogenolysis [ 36 – 39 ], making more glucose available for metabolic processes [ 36 , 37 ], as the fish rely on glycolysis to meet the demands of the body during and following TFM exposure [ 5 7 , 12 ]. In addition, glycogenolysis provides glucose-6-phosphate, which is then used as a substrate for glucuronic acid production, a major player involved in pesticide detoxification via glucuronidation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, chronically elevated cortisol in fish can negatively impact the endocrine response to stressors long-term, leading to effects on gamete quality, survivability, progeny performance and may impact the overall social status and parental care ability of the adults. In addition, TFM leads to an increased reliance on anaerobic glycolysis to make up for shortfalls in ATP supply [ 6 , 7 , 12 ], and, if applied in the presence of additional exogenous stressors (e.g. adverse environmental conditions or food deprivation), it is possible that a fishes’ability to handle such stressors could be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…All sample sites fell within the range of the tributary that was treated. Exposure to TFM usually occurs over 12 hours for maximum lethality (Clifford et al, 2012) and TFM concentrations for 2017 treatments were designed to eliminate 93% of the larvae in the population (Sullivan and Mullett, 2018).…”
Section: Mots-clés : Adn Environnemental (Edna) / Lamproie Marine / Ementioning
confidence: 99%